Synthesis of bismuth oxide nanoparticles at 100 degrees C - Patil, M. M.; Deshpande, V. V.; Dhage, S. R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of ultrafine Bi2O3 particles at 80-100 degrees C under refluxing conditions. Freshly prepared bismuth hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 6-12 h. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. The thermal decomposition of bismuth hydroxide yields Bi2O3 only at 400 degrees C. This shows the advantage of the present method. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these oven-dried powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis of Ce0.75Zr0.25O2 at 100 degrees C - Dhage, S. R.; Gaikwad, S. R.; Muthukumar, P.; Ravi, V. (Ceramics International, 2005)
A simple gel to crystal conversion route has been used for the preparation of Ce0.75Zr0.25O2 phase at 80-100degreesC under refluxing conditions. Freshly prepared metal hydroxides gel from cerium and zirconium salt solution is allowed to crystallize under refluxing and stirring conditions for 4-10 h. Formation of nano crystallites of Ce0.75Zr0.25O2 is confirmed by X-ray diffraction (XRD). Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 5 nm. (C) 2004 Elsevier Ltd and Techna S.r.l. All rights reserved.
Keywords: CeO2; chemical preparation; Electron microscopy; powders; X-ray methods

Synthesis of fine particles of ZnO at 100 degrees C - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of fine ZnO at 80-100 degreesC under refluxing conditions. Freshly prepared zinc hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 4-6 It. Formation of fine crystallites of ZnO is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for these powders. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis of Sr0.5Ba0.5Nb2O6 by urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of SrCl2, BaCl2, NbF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath.. This precipitate on decomposition at 750 degreesC yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). This is much lower temperature as compared to that prepared by traditional solid state method (1000 degreesC as reported for the formation of SBN ceramics. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1050. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides